(untitled) (Central Medical College Journal, 2024)
Background: In Bangladesh esophageal carcinoma is the leading malignant condition. Mortality rate of esophageal cancer is very high. Like other malignancies, early detection offers the best prognosis for esophageal carcinoma. Regular endoscopic and histologic surveillance have become standard procedure for follow up of patients with premalignant lesions. Objectives: The aim of this study was to evaluate the frequency and pattern of esophageal lesions with respect to age and sex groups and to determine the trends of histology, site distribution and risk factors of it. Methods: This study was a cross sectional study, carried out at the department of Pathology in Dhaka Medical College and Hospital from March 2018 to February 2020. Total 54 cases of esophageal biopsy were included in this study. All obtained samples were selected for routine histopathological study. Results: Most of the patients were male and mean age was 55.04 (±15.48) years. Squamous cell carcinoma was the most common malignancy seen in (26 cases) 48.15 % of patients and Barrett’s esophagus was common (13 cases, 24.07%) premalignant lesion. Maximum malignant and premalignant lesions (40 cases, 74.07%) were located in lower thoracic region of esophagus including gastro esophageal junction. Dysphagia was the main presenting complain in 96.3% of patients and 55.6% of patients were smoker. Conclusion: Barrett’s esophagus was the common premalignant lesion and squamous cell carcinoma was the commonest esophageal carcinoma followed by adenocarcinoma. Central Medical College Journal Vol 7 No 1 January 2023 Page: 20-25